Challenges in Determining the Cause of Death in Cardiac-related Sudden Death: A Case Report - Dhivagar K; Perumal P; Vidya M; Manoranjan B; Vinay Bannur (Journal of Indian Academy of Forensic Medicine, 2026)
Sudden cardiac death (SCD) is an unexpected natural death due to cardiac causes occurring within a short time, usually within one hour of symptom onset. Determining the exact cause of death in such cases may be challenging, particularly when deaths occur outside hospital settings and clinical history is limited. Autopsy examination plays a crucial role in identifying the underlying pathology and establishing the cause of death. This case report describes a 35-year-old male who allegedly collapsed at home and was brought dead to a tertiary care hospital. The deceased had no known history of hypertension, diabetes, or smoking but had a positive family history of ischemic heart disease. Medico-legal autopsy revealed a markedly enlarged heart weighing approximately 710 g with significant atherosclerotic narrowing of multiple coronary arteries, including 75% narrowing of the left anterior descending artery and posterior descending artery. Histopathological examination demonstrated necrotic myocardial fibers with inflammatory infiltrates and granulation tissue suggestive of myocardial infarction approximately 7–10 days old. This case highlights the importance of meticulous autopsy and histopathological examination in establishing the cause of SCD.